Navigating play: gaming experience and ad avoidance of in-game mobile ads - Syed Muhammad Fahim; Saima Munawar; Muhammad Irshad Buledi; Wong Chee Hoo; Tuba Khan (Discover Sustainability)
Abstract Game users generally avoid advertisements placed in the game environment because of the distraction created. However, game developers and advertisers aim toward the higher acceptance of ads. Such a situation creates a dichotomy of interests among the stakeholders. This study aims to conduct an empirical analysis to test the theoretical relationship between gaming experience and avoidance of in-game mobile advertisements. Additionally, it explains the parallel, serial, and conditional mediation of attitudes toward games and the attitudes towards the advertisements between gaming experience and ad avoidance. Moreover, this study assesses the interaction effect of the fear of COVID-19 on the relationship between gaming experience and the attitude towards games. Data is collected from 508 Generation Z respondents from Pakistan who regularly play games on a mobile device. The data is analyzed using the partial least squares structural equation modeling. Results reveal that gaming experience has no direct relationship with ad avoidance but indirectly affects ad avoidance through attitudes towards games and advertisements. The fear of COVID-19 moderates the relationship between attitude towards games, attitude towards advertisements, and in-game ad avoidance. At a higher level of fear of COVID-19, ad avoidance behavior is also high. This study contributes to the literature by applying conditional mediation analysis to understand the moderating role of fear of COVID-19, offering actionable insights for marketers seeking to optimize ad engagement strategies in gaming environments.